Neutrophils from F508del cystic fibrosis patients produce IL-17A and express IL-23 - dependent IL-17RC - Taylor, Patricia R (Clinical immunology (Orlando, Fla.), 2016)
Copyright © 2016 Elsevier Inc. All rights reserved.